Features of the manifestation of tic-born infections in certain regions of the Russian Federation in connection with global climate warming - Rubtsova, Irina; Malkova, Irina; Semakina, Alsu; Petukhova, Larisa (Journal of the Belarusian State University. Ecology, 2023)
On the example of many regions of the Russian Federation (Udmurt Republik, Perm Territory, Sverdlovsk Region and some others), information is confirmed that the virulence of tick-borne encephalitis viruses increases from the southwest to the northeast, as the severity of winter conditions increases. The colder the winters, the more dangerous the strain of the pathogen and the more severe the disease. The severity of tick-borne encephalitis increases as the «severity» of climatic conditions increases. That is, summer warming leads to the activation of ticks, the expansion of their range and an increase in the number of their bites. However, winter warming reduces the severity of the course of diseases, since the proportion of ticks containing low-virulent encephalitis viruses increases, which, in turn, reduces the incidence of the population due to mild, often not fixed forms, or the disease does not develop at all. That is, changes in hydrothermal conditions in recent decades affect the dynamics of all components of the arazitic system of tick-borne zooanthroponoses, exerting both direct and indirect influence on the level of epidemiological tension in natural foci of tick-borne infections. The spatial transformation of the natural focus is indicated by all three groups of indicators of the activity of ixodic ticks: the incidence of tick-borne zooanthroponoses in the population, the number of registered tick bites and the encrustation of the territory. As the climate warms, the incidence of CVE and ICB will continue to increase on the northern borders of the range of these infections, while in the southern parts of the range, suboptimal conditions for ixodic ticks may be created, which will lead to a decrease in the incidence of tick-borne infections in these territories. It is also possible that recurrent borreliosis fevers carried by argass ticks living in Central Asian countries may appear on the territory of the Russian Federation.